Elaboration and characterization of thin films of cobalt oxide - Bali Khadidja (University Of Eloued جامعة الوادي, 2025)
The study focuses on the deposition and characterization of thin layers of cobalt oxide (Co3O4) developed using the pneumatic spray technique. A system was developed for the deposition of materials using a compressor on a heated surface, with the precursor concentration and substrate temperature being variables that were varied. The X-ray diffraction analysis revealed polycrystalline films with a spinel-like structure, exhibiting multiple growth directions. The size of crystallites exhibited a direct correlation with both temperature and molarity. The surface morphology exhibited homogeneity and comprehensive coverage. A thorough examination of the films' optical properties revealed their capacity for absorption across the UV-Visible and NIR spectrums. Transmittance spectra revealed two fundamental absorption fronts in the visible region, indicating potential degeneration of the valence band. Electrical characteristics exhibited increased conductivity. الملخص: تركز الدراسة على ترسيب وتوصيف الطبقات الرقيقة من أكسيد الكوبالت (Co 3 O 4 ) باستخدام تقنية الرش الحراري. طور الباحثون نظامًا للإيداع باستخدام ضاغط على سطح مسخن، مع تغيير تركيز المادة السابقة ودرجة حرارة الركيزة. كشفت تحليل حيود الأشعة السينية عن أفلام متعددة البلورات ذات بنية تشبه السبينل، مع اتجاهات نمو متعددة. حجم البلورات الصغيرة اختلف مع درجة الحرارة والتركيز. كانت مورفولوجيا السطح متجانسة ومغطاة بشكل جيد. كما أظهرت الخصائص البصرية أن الأفلام كانت عموما ماصة في نطاق الأشعة فوق البنفسجية-المرئية والأشعة تحت الحمراء القريبة. كشفت طيفيات النفاذية عن جبهتين أساسيتين للامتصاص في المنطقة المرئية، مما يشير إلى احتمال انحلال نطاق التكافؤ. وقد أظهرت الخصائص الكهربائية زيادة في الموصلية. الكلمات المفتاحية: أفلام رقيقة من Co 3 O 4 ,الرش الحراري، التركيب السطحي، الخصائص البصرية، الخصائص الكهربائية.
Thesis
Keywords: Co3O4 thin films; Spray-Paralysis; Surface Morphology; l Optical And Electrical Properties; الأغشية الرقيقة لأكسيد الكوبات; الرش الحراري; الخصائص المورفولوجية; الخصائص الضوئية (البصرية) والكهربائية